ANALISIS PENGGUNAAN APLIKASI ALLIMNI AL-ARABIYAH DALAM MENINGKATKAN MAHARAH KALAM MAHASISWA SEMESTER 4 MA'HAD AL-BIRR UNIVERSITAS MUHAMMADIYAH MAKASSAR - Angga Riskiadin; Anshar; Muzakkir Ahlisan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
ABSTRACT This study aims to analyze the use of the Allimni Al-Arabiyah application in improving Arabic speaking skill (maharah kalam) among fourth-semester students at Ma'had Al-Birr, Universitas Muhammadiyah Makassar, and to identify the supporting and inhibiting factors in its implementation. This research employed a descriptive qualitative approach. Data were collected through in-depth interviews with fifteen fourth-semester students and the program coordinator lecturer, complemented by observation and documentation, then analyzed using the Miles and Huberman interactive model comprising data reduction, data display, and conclusion drawing. The results show that the application is used intensively, with most students accessing it four to five times a week for one and a half to two hours per session, initially based on institutional direction before gradually developing into independent use. The listening, vocabulary, and live-class features with native Arabic-speaking instructors were the most utilized, with the live class proving most influential on speaking ability; fourteen of the fifteen respondents reported noticeable improvement in fluency, pronunciation accuracy, and mastery of authentic Arabic dialect. Three main supporting factors were identified: institutional policy support, comprehensiveness of the application's features, and flexibility of learning time and place. Meanwhile, three categories of inhibiting factors emerged: technical and infrastructure constraints, particularly unstable internet connection experienced by all respondents; pedagogical limitations related to the absence of real-time pronunciation correction; and economic factors along with fluctuating motivation linked to subscription costs and academic workload. These findings indicate that Allimni Al-Arabiyah effectively supports the development of speaking skill within a boarding-school (ma'had) environment, provided it is integrated with direct conversational practice and consistent institutional policy.